PEMBERIAN SALEP KUNYIT DAPAT MENGURANGI STRIAE GRAVIDARUM PADA IBU NIFAS - Syahroni Damanik; Rauda Rauda (JKM (Jurnal Kebidanan Malahayati), 2021)
GIVING Turmeric Ointment MAY REDUCE STRIAE GRAVIDARUM IN THE PUPERATIVE MOTHER Background:Striaegravidarum is a sign or stretch that occurs on the skin of 50% to 90% of women during the second half of pregnancy. Nearly half of women experience stretching of the skin, especially in the abdomen, as a result of increasing gestational age.The presence of striae gravidarum causes a lack of self-confidence in the post-partum mother, so this makes the postpartum mother have to undergo medication and even surgery to restore her skin to the state before she was pregnant.The purpose: of this study was to determine the effect of turmeric ointment in reducing Striaegravidarum in postpartum mothers at the Hj. DewiSesmeraS.Tr.Keb Aluminum IV TanjungMulia Medan in 2020.Methods: This study used a Quasy Experiment Design (Quasi-Experimental Design) using a One Group Pretest-Postest Design. The population and sample in this study were all postpartum mothers with 15 people. This study used Porposive sampling technique with univariate and bivariate analysis with T Test.Results: the research obtained from data analysis with the Wilcoxon test showed that post-partum mothers could conclude pre-test and post-test giving turmeric ointment. The results in the table show that the P-Value (0.001) <α 0.05 then Ho is rejected and Ha is accepted, which means that there is an effect of pre-test and post-test on the administration of turmeric ointment in reducing striaegravidarum.Conclusion: This study shows that there is an effect of turmeric ointment in reducing striaegravidarum. Suggestions for the clinic mother Hj. Dewi Sesmera so that mothers can advise postpartum mothers to make their own products with ingredients derived from traditional turmeric in reducing striaegravivarum. Keywords: Key words: Turmeric ointment, Striae gravidarum, postpartum mother